1978
DOI: 10.2466/pms.1978.46.3c.1107
|View full text |Cite
|
Sign up to set email alerts
|

Intercorrelations among Tests of General Mental Ability and Achievement for Black and White Deaf Children

Abstract: The purpose of this study was to compare the relative effectiveness of two measures commonly used to predict school achievement of black and white deaf children. The Wechsler Intelligence Scale for Children-Revised and the Hiskey-Nebraska Test of Learning Aptitude correlated significantly with Stanford Achievement Test scores for 23 black children but not for 36 white. Even though the groups differed significantly in WISC-R Performance IQ, Hiskey learning quotient, and in CA, they did not differ in achievement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Utilizing black (N=36) and white (N=30) children, they concluded that there were not significant differences in the regression lines between the groups, therefore a common regression line could be used for both intellectual measures. Hirshoren, Hurley, and Hunt (1977) and Hurley, Hirshoren, Kavale, and Hunt (1978) examined correlations between the WISC-R and the HiskeyNebraska Test of Learning Aptitude (H-NTLA) (Hiskey, 1966), which was developed for use and standardized with deaf or hearing impaired students. Although both studies utilized the same sample of 59 prelingually deaf students, the latter study also examined the correlation of these two measures with the Stanford Achievement Test (SAT) and the differing levels of performance between black and white deaf children.…”
Section: Concurring Withmentioning
confidence: 99%
“…Utilizing black (N=36) and white (N=30) children, they concluded that there were not significant differences in the regression lines between the groups, therefore a common regression line could be used for both intellectual measures. Hirshoren, Hurley, and Hunt (1977) and Hurley, Hirshoren, Kavale, and Hunt (1978) examined correlations between the WISC-R and the HiskeyNebraska Test of Learning Aptitude (H-NTLA) (Hiskey, 1966), which was developed for use and standardized with deaf or hearing impaired students. Although both studies utilized the same sample of 59 prelingually deaf students, the latter study also examined the correlation of these two measures with the Stanford Achievement Test (SAT) and the differing levels of performance between black and white deaf children.…”
Section: Concurring Withmentioning
confidence: 99%